Gadolinium-Induced Acute Graft Pancreatitis in a Simultaneous Pancreas-Kidney Transplant Recipient. (21st August 2022) - Lee, Chiang Sheng; Tan, Rachel Yi Ping; Rao, Nitesh N.
Abstract : Gadolinium-induced acute pancreatitis is a rare phenomenon associated with the administration of gadolinium-based contrast agents. Only five cases of gadolinium-induced acute pancreatitis have been reported worldwide in patients with native pancreas and none with a pancreatic graft. We present a 32-year-old woman with prior history of simultaneous pancreas-kidney transplant who presented with generalized abdominal pain associated with systemic inflammatory response syndrome requiring admission to the intensive care unit. This occurred within 48 hours after having a magnetic resonance imaging (MRI) with gadolinium for investigation of subacute left optic atrophy. She was noted to have a marked rise in serum lipase, and the computed tomography findings were consistent with acute graft pancreatitis. Other causes of pancreatitis were ruled out, and she was managed conservatively with aggressive hydration, bowel rest, and analgesia with good recovery. This is the first reported case of gadolinium-induced acute graft pancreatitis occurring in a simultaneous pancreas-kidney transplant recipient. Clinicians should consider this rare differential diagnosis as a cause of graft pancreatitis in patients who have received gadolinium-based contrast agents.